Development and Internal Validation of a Prediction Model to Risk Stratify Children With Suspected Community-Acquired Pneumonia. (7th November 2020) - Florin, Todd A; Ambroggio, Lilliam; Lorenz, Douglas; Kachelmeyer, Andrea; Ruddy, Richard M; Kuppermann, Nathan; Shah, Samir S
Abstract: Background: Although community-acquired pneumonia (CAP) is one of the most common infections in children, no tools exist to risk stratify children with suspected CAP. We developed and validated a prediction model to risk stratify and inform hospitalization decisions in children with suspected CAP. Methods: We performed a prospective cohort study of children aged 3 months to 18 years with suspected CAP in a pediatric emergency department. Primary outcome was disease severity, defined as mild (discharge home or hospitalization for <24 hours with no oxygen or intravenous [IV] fluids), moderate (hospitalization <24 hours with oxygen or IV fluids, or hospitalization >24 hours), or severe (intensive care unit stay for >24 hours, septic shock, vasoactive agents, positive-pressure ventilation, chest drainage, extracorporeal membrane oxygenation, or death). Ordinal logistic regression and bootstrapped backwards selection were used to derive and internally validate our model. Results: Of 1128 children, 371 (32.9%) developed moderate disease and 48 (4.3%) severe disease. Severity models demonstrated excellent discrimination (optimism-corrected c-indices of 0.81) and outstanding calibration. Severity predictors in the final model included respiratory rate, systolic blood pressure, oxygenation, retractions, capillary refill, atelectasis or pneumonia on chest radiograph, and pleural effusion. Conclusions: We derived and internally validated a score that accurately predicts disease severity in children with suspected CAP. Once externally validated, this score has potential to facilitate management decisions by providing individualized risk estimates that can be used in conjunction with clinical judgment to improve the care of children with suspected CAP. Abstract : In this prospective study of 1128 children with suspected CAP, we developed a well-calibrated severity score of 7 variables (respiratory rate, blood pressure, oxygenation, retractions, capillary refill, radiographic findings, pleural effusion) with excellent discriminatory ability for moderate or severe disease.